Solar Energy Support System of Mobile Robot for Exploring Disaster Area - Riza Muhida; Suhaimi B Mohd Zaid; Abdul Fatah Nordin; Yusran Tarihoran (TeIKa, 2008)
Abstract A mobile robot for exploring disaster area in tropical region has been developed. It has capability to travel over a rough irregular terrain within disaster area and capable of performing a range of functions such as collecting samples and capturing images from the disaster scene. Furthermore, the robot is equipped with solar panel for extending the operation rather than relying on rechargeable battery only. Construction of the robot consists of 2 degrees of freedom loory in robot arm, including gripper, wireless camera/ wireless RF controller and electrical controller of photovoltaic system. The robot can be controlled remotely and also has capability to send captured images wirelessly to a designated controller/server. The transmitted live images can also be used to monitor robot movement and allow real time interactions between the operator and the robot. Â  Abstrak Robot yang mampu menjelajahi lokasi bencana pada daerah tropis sudah dikembangkan. Dia memiliki kemampuan untuk bergerak di tanah yang tidak rata pada suatu daerah bencana serta mampu melakukan tugas seperti mengumpulkan contoh dan mengambil gambar-gambar pada suatu area bencanan. Robot ini selain menggunakan batre yang dapat diisi ulang juga diperlengkapi dengan energy tenaga surya sehingga daya operasinya lebih lama. Pembuatan robot ini menggunakan 2 derajat kebebasan (DOF) yaitu pada lengan robot, termasuk penjepit, kamera tanpa kabel, pengendali Rf dan pengontrol sistem elektrik photovoltaic. Robot bisa dikendalikan dari jarak jauh dan mampu untuk mengirim gambar ke server yang telah ditentukan. pergerakan robot dapat dipantau langsung melalui gambar-gambar yang dikirim dan juga dapat dikendalikan secara real time.